Cómo mejorar el papel de las TIC para promover una educación empoderadora en el desarrollo sostenible - Plaza de la Hoz, Jesús (ALOMA. Revista de Psicologia, Ciències de l'Educació de l'Esport, 2019)
INTRODUCCIÓN. Nuestro mundo en constante transformación precisa un sistema educativo que sepa adaptarse al entorno cambiante. Sostener un modo de vida más humano y solidario implica empoderar a las nuevas generaciones con las competencias digitales del siglo XXI. Se propone un estudio teórico-práctico sobre una educación empoderadora en el desarrollo sostenible que, a la vista del uso de nuevas tecnologías, permita sugerir algunas propuestas de mejora. MÉTODO. Realiza una revisión crítica de bibliografía reciente relacionada con los conceptos aludidos, y la compara con un estudio cualitativo sobre tecnologías y educación realizado con veinte estudiantes y cuarenta y ocho profesores de Educación Secundaria. Se usan entrevistas y grupos de discusión; y se analizan los datos con la ayuda del programa Atlas.ti7. RESULTADOS. Se observa un contraste respecto al ideal de Escuela 2.0: prevención de los profesores ante la inmadurez de los estudiantes, un tipo de control significativo que ambos juzgan necesario, falta de formación del profesorado y un uso instrumental de las TIC. DISCUSIÓN. La normalización de un uso adecuado de las TIC y la constante formación tecno-pedagógica del profesorado serían cauces para la empoderación del alumnado. CONCLUSIÓN. Se sugieren varias propuestas de cómo educar con TIC estudiantes conscientes de su papel en construir una sociedad sostenible.
How to improve the use of ICT to promote empowerment in education in sustainable development
INTRODUCTION. Our world is undergoing constant transformation, and it requires an education system that can adapt to meet changing needs. Our need to sustain a more fully human life and to engage in solidarity means that we must appeal to new generations using 21st century digital competences. This is a theoretical and practical study of empowering education about sustainable development. Thanks to the application of new technologies, the study was able to highlight some proposals for improving education in this regard. METHOD. First, a critical literature review was conducted of publications related to the topics of the paper. Then, a qualitative study on technology and education was conducted with 20 secondary school students and forty-eight teachers, and the results were compared with those of prior research. For the purposes of the study, interview and group discussion techniques were used, and the data collected were analysed using the program Atlas.ti7. RESULTS. The observed results contrast with the ideal of "School 2.0". Teachers engage in preventive activities due to the immaturity of the students, representing a significant type of control that both parties deem necessary, a lack of training on the part of teachers and an instrumental use of ICT. DISCUSSION. The normalisation of appropriate use of ICT and a constant process of technological and pedagogical training for teachers could help to empower students. CONCLUSION. Several suggestions are made as to how to use ICT to educate students to be aware of their roles in creating a sustainable society.
Keywords: sustainable development; empowering students; technology in education; secondary education; teachers; desarrollo sostenible; empoderamiento del estudiante; tecnología educativa; educación secundaria; profesores; Emerging; Scopus